Analysis of Education Ministry Policy Related to Education in Covid-19 Perspective of The Power of Knowledge Michael Foucault and David Ausubel’s Meaning Learning Theory - Bahroni Zainuri Yulien; Faizal Efendi (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2022)
This paper aims to analyze the policies of the Ministry of Education and Culture regarding learning and the effectiveness of E-learning during the Covid-19 period by linking Michael Foucault’s theory and ausubel theory in education during the Covid-19 period. The research method used is library research, where library techniques are carried out by studying, reading and recording various literature or reading materials that are in accordance with the subject matter. Then filtered and poured into a theoretical framework. The author also uses Michael Foucault’s power of knowledge analysis and meaningful learning by David Ausubel on the policies of the Ministry of Education and Culture in education during the Covid-19 period. The results of this study are that when viewed from the analysis of Michel Foucault’s theory, it is very clear that governmentality is a state that has the right to regulate an action or behavior of the community by internalizing an occupation so that it becomes an obedient or obedient population as a form of rationalization for the operation of a power. Meanwhile, in terms of David Ausubel’s theory, the process of linking new information in relevant concepts is contained in a person’s cognitive structure. Cognitive structure involves concepts, facts and generalizations that have been memorized and learned by students in the sense that this theory provides a meaningful learning for students